2006
DOI: 10.1530/eje.1.02267
|View full text |Cite
|
Sign up to set email alerts
|

Body composition is distinctly altered in Turner syndrome: relations to glucose metabolism, circulating adipokines, and endothelial adhesion molecules

Abstract: Background: Body composition in Turner syndrome (TS) is altered with final height of TS decreased; anthropometry and bone mass distinctly changed. Aim: To describe total and regional distribution of fat and muscle mass in TS and the relation to measures of glucose metabolism, sex hormones, IGFs, and markers of inflammation and vascular function. Material and methods: Fifty-four women with TS (mean age, 42.5G9.7 years) and an age-matched group of controls (nZ55) were examined by dual-energy X-ray absorptiometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
3
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 44 publications
11
71
3
5
Order By: Relevance
“…We also observed a tight coupling between changes in markers of bone formation and resorption, contrary to what we observed in the initial baseline study from the present cohort (4), where we found bone formation markers to be comparable or only marginally elevated in comparison with controls, while bone resorption markers were 35-70% elevated (4). In the present population, it is difficult to determine whether inadequate sex HRT or the relative secondary hyperparathyroidism is the cause of the enhanced resorption, or if it is a consequence of other metabolic changes, such as low serum testosterone (18,37) and low bioavailable IGF1 (38,39), or the genetic defect per se. The observed positive correlation between plasma PTH and total OC and renal NTX/creatinine corroborates a biological effect of PTH on bone in Turner patients.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…We also observed a tight coupling between changes in markers of bone formation and resorption, contrary to what we observed in the initial baseline study from the present cohort (4), where we found bone formation markers to be comparable or only marginally elevated in comparison with controls, while bone resorption markers were 35-70% elevated (4). In the present population, it is difficult to determine whether inadequate sex HRT or the relative secondary hyperparathyroidism is the cause of the enhanced resorption, or if it is a consequence of other metabolic changes, such as low serum testosterone (18,37) and low bioavailable IGF1 (38,39), or the genetic defect per se. The observed positive correlation between plasma PTH and total OC and renal NTX/creatinine corroborates a biological effect of PTH on bone in Turner patients.…”
Section: Discussioncontrasting
confidence: 62%
“…Regardless of BMD, end-point studies have documented increased fracture frequency in girls and women with TS (11)(12)(13). It is not entirely clear whether a primary bone defect exists in TS (4,14), perhaps due to skeletal dysmorphogenesis (15) caused by haploinsufficiency of the short stature homeoboxcontaining gene (SHOX) (16,17) or rather endocrine or metabolic defects exists (18), resulting in estrogen deficiency and other endocrine deficiencies (4).…”
Section: Introductionmentioning
confidence: 99%
“…nography (18), DXA (19,20), BIA (21,22) and magnetic resonance imaging (23). If, on the one hand they produce high-quality information on the other some of these instruments are relatively expensive and have little mobility (24).…”
Section: Discussionmentioning
confidence: 99%
“…However, proinflamatory cytokines, interleukin-6, interleukin-8 and tumor necrosis factor α may be partly responsible for that (29,30). Su and cols.…”
Section: Autoimmune Disordersmentioning
confidence: 99%